Single-Molecule Traps in Covalent Organic Frameworks for Selective Capture of C2H2 from C2H4-Rich Gas Mixtures - Yilun Zhou; Yinghui Xie; Xiaolu Liu; Mengjie Hao; Zhongshan Chen; Hui Yang; Geoffrey I. N. Waterhouse; Shengqian Ma; Xiangke Wang (Research, 2024)
Removing trace amounts of acetylene (C2H2) from ethylene (C2H4)-rich gas mixtures is vital for the supply of high-purity C2H4 to the chemical industry and plastics sector. However, selective removal of C2H2 is challenging due to the similar physical and chemical properties of C2H2 and C2H4. Here, we report a “single-molecule trap” strategy that utilizes electrostatic interactions between the one-dimensional (1D) channel of a covalent organic framework (denoted as COF-1) and C2H2 molecules to massively enhance the adsorption selectivity toward C2H2 over C2H4. C2H2 molecules are immobilized via interactions with the O atom of C=O groups, the N atom of C≡N groups, and the H atom of phenyl groups in 1D channels of COF-1. Due to its exceptionally high affinity for C2H2, COF-1 delivered a remarkable C2H2 uptake of 7.97 cm3/g at 298 K and 0.01 bar, surpassing all reported COFs and many other state-of-the-art adsorbents under similar conditions. Further, COF-1 demonstrated outstanding performance for the separation of C2H2 and C2H4 in breakthrough experiments under dynamic conditions. COF-1 adsorbed C2H2 at a capacity of 0.17 cm3/g at 2,000 s/g when exposed to 0.5 ml/min C2H4-rich gas mixture (99% C2H4) at 298 K, directly producing high-purity C2H4 gas at a rate of 3.95 cm3/g. Computational simulations showed that the strong affinity between C2H2 and the single-molecule traps of COF-1 were responsible for the excellent separation performance. COF-1 is also robust, providing a promising new strategy for the efficient removal of trace amounts of C2H2 in practical C2H4 purification.